2017
DOI: 10.1063/1.4977951
|View full text |Cite
|
Sign up to set email alerts
|

Small-world bias of correlation networks: From brain to climate

Abstract: Complex systems are commonly characterized by the properties of their graph representation. Dynamical complex systems are then typically represented by a graph of temporal dependencies between time series of state variables of their subunits. It has been shown recently that graphs constructed in this way tend to have relatively clustered structure, potentially leading to spurious detection of small-world properties even in the case of systems with no or randomly distributed true interactions. However, the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The rationale behind this was that these measures are only meaningful in connected networks 1 , and the subsampled binary graphs in this study were generally disconnected at network densities ≤25%. A method to circumvent this issue is to only compute the measures on the fully connected subgraph within the network 38 , 39 . However, this would mean that when comparing two group networks it is likely that their respective (fully connected) subgraphs would be of different sizes and consist of different nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this was that these measures are only meaningful in connected networks 1 , and the subsampled binary graphs in this study were generally disconnected at network densities ≤25%. A method to circumvent this issue is to only compute the measures on the fully connected subgraph within the network 38 , 39 . However, this would mean that when comparing two group networks it is likely that their respective (fully connected) subgraphs would be of different sizes and consist of different nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, some features of the investigated network are preserved in the reference random network. Hlinka et al ( 2017 ) demonstrated that the model process with randomly scrambled interconnections reveals SW features similar to the ones of the original time series.…”
mentioning
confidence: 98%
“…Note that this is actually in line with the Occam’s razor requirement of simple explanation - see the section Proofs for the proof concerning the 3-variable case; showing that the least presumptive solution is for two of three variables to be conditionally mutually independent. The fact that the current method provides network estimates with low clustering, and therefore without small-world properties, is not too detrimental in the light of recent observations that the small-world properties of the functional connectivity of many real-world systems are spurious 47 , as recently documented for the example of brain and climate data 48 .…”
Section: Discussionmentioning
confidence: 82%